Nanotechnologies - Wautelet, M. (London, United Kingdom The Institution of Engineering and Technology, 2009)
The book reviews developments in the following fields: the nanotechnology revolution; atomic structure and cohesion; electronic structures of nanosystems; molecular electronics; neuroelectronics; plastic electronics; fabrication of nanostructures; organic-matrix-based nanocomposites; nanomagnetism; and nanotechnologies in perspective.
Also available in print version.
Electronic reproduction.
Keywords: Nanotechnology; Electronic structure; Magnetic materials; Microfabrication; Molecular electronics; Nanocomposites (Materials).; Nanoelectronics; Nanostructured materials; Electronic books